2019
DOI: 10.1007/s11357-019-00084-0
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic conversion of proliferative astroglia into neurons after cerebral ischemia: a new therapeutic tool for the aged brain?

Abstract: Ischemic stroke represents the 2nd leading cause of death worldwide and the leading cause for long-term disabilities, for which no cure exists. After stroke, neurons are frequently lost in the infarct core. On the other hand, other cells such as astrocytes become reactive and proliferative, disrupting the neurovascular unit in the lesioned area, especially in the aged brain. Therefore, restoring the balance between neurons and nonneuronal cells within the perilesional area is crucial for post stroke recovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Despite the originality of our study, some limitations should be acknowledged. First, we explored intracellular Ca 2+ dysregulation as the only factor contributing to the pathogenesis of aging and not other hypotheses such as: (i) glial cell alterations (Popa-Wagner et al, 2019 ), (ii) blood-brain-barrier disruption (Fulop et al, 2019 ), (iii) alteration in circadian rhythms (Logan et al, 2018 ), and (iv) endothelial dysfunction (Tarantini et al, 2019 ). Second, we did not perform a dose-response curve on dantrolene and cognitive improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the originality of our study, some limitations should be acknowledged. First, we explored intracellular Ca 2+ dysregulation as the only factor contributing to the pathogenesis of aging and not other hypotheses such as: (i) glial cell alterations (Popa-Wagner et al, 2019 ), (ii) blood-brain-barrier disruption (Fulop et al, 2019 ), (iii) alteration in circadian rhythms (Logan et al, 2018 ), and (iv) endothelial dysfunction (Tarantini et al, 2019 ). Second, we did not perform a dose-response curve on dantrolene and cognitive improvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, in response to cerebral ischemia, a growing number of studies have found that astrocytes in the striatum can be transformed into neurons. 32 33 Both in vivo and in vitro studies have shown that astrocytes have the characteristics of stem cells and can differentiate into neurons under certain conditions 34 35 36 37 ( Figure 2 ).…”
Section: Astrocyte-mediated Neurogenesis After Ischemic Strokementioning
confidence: 99%
“…A1 astrocytes are derived from resting astrocytes stimulated by the inflammatory factors including TNF-α, IL-1α, and C1q generated from activated microglia (Liddelow et al, 2017), and A1 astrocyte has been ascertained to be elevated after cerebral ischemia. A1 activated astrocyte not only delivery inflammatory mediators, such as TNF-α, IL-1, glial fibrillary acidic protein (GFAP), and matrix metalloproteases (MMPs), but also promote the formation of glial scar and disrupt the BBB (Jayaraj et al, 2019;Popa-Wagner et al, 2019). Meanwhile, the infiltrated neutrophils, DCs, and lymphocytes also promote proinflammatory pathways via secreting inflammatory factors and endothelial adhesion molecules (Weston et al, 2007;Anrather and Iadecola, 2016).…”
Section: Inflammatory Activitymentioning
confidence: 99%